“Old dirty pops and young hot chicks”: Age differences in pornographic fantasies - Paasonen Susanna (Routledge, 2022)
As a genre, pornography has long highlighted embodied differences and juxtaposed different bodies in terms of their size, degrees of hairiness or muscularity, skin colour and tone. Building on a 2017 survey charting pornographic preferences, likes and dislikes among Finnish women, this chapter focuses on age differences in particular and investigates the ageing male body as an ambivalent, simultaneously attractive and repulsive pornographic fantasy figure. It asks how age differences feed into dynamics of control and submission in pornographic imageries, how ageing bodies function as markers of extremity and authenticity and how the survey respondents, the majority of them in their twenties and thirties, negotiate gaps between their pornographic preferences and other sexual likes. Emphasising the specific role and function of sexual fantasies, the respondents describe the appeal of older male bodies as sites of disgust and taboo transgression to be enjoyed from a distance, and the scenarios they enjoy as drawing their force from social hierarchies and from breeching the norms of sexual acceptability and normalcy.
Gender and sexuality in the European Media: Exploring Different Contexts through Conceptualisations of Age